Physicochemical Characteristics of Catfish (Clarias sp) Sausage with Addition of Moringa Leaf Flour (Moringa oleifera) - Septiani Dwi Rahayu; Rizky Muliani Dwi Ujianti; Fafa Nurdyansyah (Advance Sustainable Science, Engineering and Technology (ASSET), 2022)
Sausage is a processed food product that is generally made of meat, fat, filler, water, binder and salt. Catfish is a source of animal protein that has advantages compared to other animal products, namely catfish which is rich in lysine, and leucine. Moringa leaf flour is Moringa leaves that are given drying, milling treatment to facilitate processing into various food products and as a fortification material with high nutrition. This study aims to determine the effect of differences in concentration of catfish: tapioca flour with the addition of Moringa leaf flour on the physicochemical properties of catfish sausage. The results obtained in the study that the difference in the concentration of catfish: tapioca flour and the addition of Moringa leaf flour affect the analysis of water content 58%; fat content 13%; ash content 1.85%; protein content 18.09%; color parameter L* 47,26-66,48; color parameter a* (-4.43)-5.40; color parameter b* 14.25-26.71.